2017
DOI: 10.1212/wnl.0000000000003510
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-associated worsening in reversible cerebral vasoconstriction syndrome

Abstract: Objective: Factors predicting poor outcome in patients with the reversible cerebral vasoconstriction syndrome (RCVS) have not been identified. Methods:In this single-center retrospective study, we analyzed the clinical, brain imaging, and angiography data in 162 patients with RCVS. Univariable and multivariable regression analysis were performed to identify predictors of persistent (nontransient) clinical worsening, radiologic worsening, early angiographic progression, and poor discharge outcome (modified Rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 32 publications
(67 reference statements)
4
101
0
14
Order By: Relevance
“…Calcium channel‐blocker therapy (nimodipine) may be discussed as a vasoactive drug, with cautious use and close monitoring because of systemic action, and hence the risk of precipitously dropping systemic blood pressure and causing cerebral ischaemic injury. A recent study showed that corticosteroids could worsen RCVS outcome . Therefore, in the setting of SLE or SLE flare‐up, acute neurological symptoms should lead to complete brain imaging, including cerebral angiography, and specific tests to rule out subarachnoid haemorrhage (CSF analysis with spectro‐photometry for xanthochromia and/or gradient echo magnetic resonance sequencing).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium channel‐blocker therapy (nimodipine) may be discussed as a vasoactive drug, with cautious use and close monitoring because of systemic action, and hence the risk of precipitously dropping systemic blood pressure and causing cerebral ischaemic injury. A recent study showed that corticosteroids could worsen RCVS outcome . Therefore, in the setting of SLE or SLE flare‐up, acute neurological symptoms should lead to complete brain imaging, including cerebral angiography, and specific tests to rule out subarachnoid haemorrhage (CSF analysis with spectro‐photometry for xanthochromia and/or gradient echo magnetic resonance sequencing).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that corticosteroids could worsen RCVS outcome. 11 Therefore, in the setting of SLE or SLE flare-up, acute neurological symptoms should lead to complete brain imaging, including cerebral angiography, and specific tests to rule out subarachnoid haemorrhage (CSF analysis with spectrophotometry for xanthochromia and/or gradient echo magnetic resonance sequencing).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the diagnostic workup showed a complete restitution of cerebral artery vasoconstriction within 4 weeks to 3 months which could be excluded to appear in PACNS without immunosuppressive therapy. Furthermore, RCVS patients are at risk of neurological worsening if treated with glucocorticoids, which will mainly be the firstline therapy in suspected cerebral vasculitis [9]. However, a conclusive interpretation is lacking in the literature, as well as the discussion of whether the diagnostic criterion of CSF leucocyte counts < 10/mm 3 should be maintained.…”
Section: Discussionmentioning
confidence: 99%
“…[45] This possibility has also been raised for a related disorder – reversible cerebral vasoconstriction syndrome. [44] Alternatively, it is plausible that steroid administration simply reflects the presence of an underlying inflammatory or oncological disease, which may itself cause PRES through endothelial dysfunction [2]. However, were this the case, we would expect to find less vasogenic edema in patients receiving steroids.…”
Section: Discussionmentioning
confidence: 99%